PEMBERDAYAAN MASYARAKAT PENCEGAHAN DINI PENYAKIT ASAM URAT DI POSBINDU DESA PELEMAN GEMOLONG - Sulistyowati, Dwi; Rita Benya Adriani; Suryanti, Suryanti (Tahta Media Grup, 2025)
Gout as a type of inflammatory arthritis caused by the deposition of monosodium urate crystals contained in synovial fluid. Gout can cause a decrease in the quality of life for sufferers, because people who experience gout will feel pain that interferes with activity and comfort. Early prevention is an important step to reduce the incidence of this disease, especially through a community empowerment approach. Community empowerment activities aim to determine the description of the quality of life of the elderly who experience gout. This community service uses a descriptive type that aims to determine the description of the quality of life of the community / elderly who experience gout with a survey approach. This approach was carried out at Posbindu Peleman Village, Gemolong District, Sragen Regency. Community service was carried out during July December 2024. The results of community service show that 70% of the community has done the right diet, and 30% of the community still has difficulty living a healthy life. The conclusion of community service shows a significant increase in the understanding and skills of the community in early prevention of gout.